Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Reactivity and operational stability of N-Tailed TAMLs through kinetic studies of the catalyzed oxidation of orange II by H2O2: synthesis and x-ray structure of an N-Phenyl TAML - Warner, Genoa R.; Mills, Matthew R.; Enslin, Clarissa; Pattanayak, Shantanu; Panda, Chakadola; Panda, Tamas Kumar; Sen Gupta, Sayam; Ryabov, Alexander D.; Collins, Terrence J. (Chemistry A-European Journal, 2015)
{The catalytic activity of the N-tailed (biuret) TAML (tetraamido macrocyclic ligand) activators [Fe{4-XC6H3-1,2-(NCOCMe2NCO)(2)NR}Cl](2-) (3; N atoms in boldface are coordinated to the central iron atom; the same nomenclature is used in for compounds 1 and 2 below), [X
Keywords: Hydrogen peroxide; iron; kinetics; Oxidation; reaction mechanisms